An AIE‐Active Ultrathin Polymeric Self‐Assembled Monolayer Sensor for Trace Volatile Explosive Detection. Issue 23 (3rd December 2021) - Li, Mingliang; Xie, Kefeng; Wang, Guozhi; Zheng, Jing; Cao, Yingnan; Cheng, Xiang; Li, Ziwei; Wei, Feng; Tu, Hailing; Tang, Jinyao
Abstract : Front Cover : Based on the aggregation‐induced emission (AIE) effect, an ultra‐thin self‐assembled monolayer (SAM) sensor for trace nitro explosives is designed by Ziwei Li, Feng Wei, Jinyao Tang, and co‐workers, in article 2100551 . The polymeric SAMs are fabricated by covalent bonds to the substrate, and prove to show good stability, sensitivity, selectivity, and reversibility. The sensing properties are further improved by being coated on Al2 O3 fiber paper, which realizes the detection by the naked eye.